Examination of social media usage habits of generation Z - Elkatmış, Metin (Frontiers in Psychology, 2024)
Undoubtedly, social media is one of the significant components of computer and internet technologies. It offers users the opportunity to share emotions, thoughts, and life experiences through various means such as text, images, and videos on the internet. In doing so, it not only provides a multifaceted communication and interaction opportunity for users of all ages but also creates a dynamic and entertaining parallel universe. This universe shapes and transforms individual, social, and cultural life, as well as habits. With the daily increase in user numbers, social media has become an integral part of our lives. The primary objective of this study is to determine the social media usage habits of fourth-grade students, known as Generation Z. The research was conducted using semi-structured interviews, a qualitative data collection method. The universe of the study consisted of 654 fourth-grade students attending state schools in seven different provincial centers representing the seven geographical regions of Turkey during the 2021-2022 academic year. The data were collected using an interview form developed for this research and analyzed with the content analysis technique. According to the research findings, it was determined that approximately three-quarters of primary school fourth-grade students use social media on a daily basis. Moreover, most participants stated that they use social media for educational, communicative, and entertainment purposes. The most preferred social media platforms by students were identified as YouTube, WhatsApp, TikTok, and Instagram.